The negative effects of mismanagement of zakat on the achievement of its objectives - Tahir, Ibrahim Nuhu (2016)
Zakat is one of the five pillars of Islam and even though it’s a system designed by Allah The Almighty it has faced many challenges across the centuries when it comes to its application. The main objectives of zakat were well achieved during the early generations, from the time of the Prophet to the time of the Rightly Guided Caliphs. This success was a result of strict adherence to the text of Shari'ah which are supposed to be understood literally in this matter. For examples, instances were reported in some areas where people reached the level of satisfaction which removed them from poverty. However this is not the case in our contemporary era where mismanagement of zakat occurs due to interference by those in authority and inappropriate ijtihad which have become obstacles that hinder the achievement of the objectives of the zakat system. The system is divinely revealed by Allah and this is proof of its perfection and accuracy and thus needs no modification or change. The paper focuses on certain key issues of concern in managing the collection, preservation and distribution of zakat.